Penggunaan E-Learning Berbasis Edmodo Terhadap Hasil Belajar Kelas 4 Sekolah Dasar - Zyra, Sidra Nur; Alamsyah, Trian Pamungkas; Yuliana, Rina (UNIB Press, 2022)
The increasing number of pandemic cases has an impact on the education sector. This study aims to determine whether the learning outcomes of students who use Edmodo are better than students who use Google Classroom. The method in this research is an experimental method with a quasi-experimental design. This method is an experimental based quantitative method to show whether there is an effect on the independent variable (treatment) to the dependent variable (results) in a controlled situation. The results of this study indicate the difference in the average learning outcomes of 78 for the experimental class and 56,5 for the control class. This is evidenced by the value of the different test results (t) from the above calculation it is obtained that tcount 3,74 and ttabel 1,68, which means that H0 is rejected and Ha is accepted. This indicates that the learning outcomes of students in the experimental class are better than students in the control class.